Bortezomib-Dexamethasone, Rituximab, and Cyclophosphamide as First-Line Treatment for Waldenström's Macroglobulinemia: A Prospectively Randomized Trial of the European Consortium for Waldenström's Macroglobulinemia - Buske, Christian; Dimopoulos, Meletios A; Grunenberg, Alexander; Kastritis, Efstathios; Tomowiak, Cecile; Mahé, Béatrice; Troussard, Xavier; Hajek, Roman; Viardot, Andreas; Tournilhac, Olivier; Aurran, Therese; Lepretre, Stephane; et al. (Journal of clinical oncology, 2023)
PURPOSE: Rituximab/chemotherapy is a cornerstone of treatment for Waldenström's macroglobulinemia (WM). In addition, bortezomib has shown significant activity in WM. This study evaluated the efficacy and safety of dexamethasone, rituximab, and cyclophosphamide (DRC) as first-line treatment in WM. METHODS: In this European study, treatment-naïve patients were randomly assigned to DRC or bortezomib-DRC B-DRC for six cycles. The primary end point was progression-free survival. Secondary end points included response rates, overall survival, and safety. RESULTS: Two hundred four patients were registered. After a median follow-up of 27.5 months, the estimated 24-month progression-free survival was 80.6% (95% CI, 69.5 to 88.0) for B-DRC and 72.8% (95% CI, 61.3 to 81.3) for DRC (P = .32). At the end of treatment, B-DRC and DRC induced major responses in 80.6% versus 69.9% and a complete response/very good partial response in 17.2% versus 9.6% of patients, respectively. The median time to first response was shorter for B-DRC with 3.0 (95% CI, 2.8 to 3.2) versus 5.5 (95% CI, 2.9 to 5.8) months for DRC. This resulted in higher major response rates (57.0% v 32.5%; P < .01) after three cycles of B-DRC compared with DRC. At best response, the complete response/very good partial response increased to 32.6% for B-DRC. Both treatments were well tolerated: grade ≥ 3 adverse events occurred in 49.2% of all patients (B-DRC, 49.5%; DRC, 49.0%). Peripheral sensory neuropathy grade 3 occurred in two patients treated with B-DRC and in none with DRC. CONCLUSION: This large randomized study illustrates that B-DRC is highly effective and well tolerated in WM. The data demonstrate that fixed duration immunochemotherapy remains an important pillar in the clinical management of WM.
Keywords: Waldenstrom Macroglobulinemia; Cyclophosphamide; Dexamethasone; lidé; Waldenströmova makroglobulinemie; cyklofosfamid; Bortezomib; rituximab; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; bortezomib; Rituximab; dexamethason